The Dyeing of Cotton Fabric with Natural Dye from Buddlejae Flos. Issue 12 (2nd December 2022) - Ke, Guizhen; Chen, Shuhui; Zheng, Youwei; Zhao, Ziying; Tang, Jiani; Peng, Feifan
ABSTRACT: Buddlejae Flos is a promising natural dye for cotton fabric. Buddlejae Flos extraction and AlK(SO4 )2 .12H2 O were dissolved in 70% ethanol and the cotton fabric was dyed with this solution. And its dyeing kinetics and isotherm were evaluated. The results showed that dye absorption increased with the increase in dye concentration and dyeing temperature. The absorption kinetics of Buddlejae Flos dye onto cotton fabric were best described by the pseudo-second-order kinetics model (R 2 > 0.99) and absorption isotherm fitted the Freundlich model better. Optimal dyeing conditions were selected through orthogonal trial: 1:30 bath ratio, 80°C dyeing temperature, 100 min dyeing time, and 1.25 g/L mordant. The Buddlejae Flos dyed cotton fabric presented good antioxidant performance. The wash fastness and rubbing fastness of the dyed cotton fabric are both above 4 grades. It is concluded that Buddlejae Flos has a good potential to act as a source of natural colorant for cotton dyeing in the ethanol-water system.